Multikulturalisme dan Resolusi Konflik dalam Pendidikan Islam di Era Globalisasi - Iqbal, Muhammad (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
In the era of globalization, cultural diversity and international interactions are increasing, requiring the education system, including Islamic education, to adapt to these dynamics. This article explores the integration of multiculturalism and conflict resolution in Islamic education, focusing on the challenges and opportunities faced in an increasingly pluralistic global context. Multiculturalism in Islamic education seeks to respect and accommodate cultural diversity without sacrificing core religious values. Meanwhile, conflict resolution plays an important role in managing differences and tensions that arise in a multicultural educational environment. This article discusses effective approaches in integrating the values of multiculturalism into the Islamic education curriculum, training for educators, and community participation. Case studies from countries that have implemented best practices are also analyzed to provide insight into successful strategies. The findings show that effective application of the principles of multiculturalism and conflict resolution can strengthen the quality of Islamic education and prepare students to interact positively in a diverse global society. Recommendations are proposed for curriculum development, teacher training, and educational policies to support inclusion and harmony in Islamic education.